DNA MemoChip: Long-Term and High Capacity Information Storage and Select Retrieval - Stefano, George B; Wang, Fuzhou; Kream, Richard M (Medical Science Monitor, 2018)
Over the course of history, human beings have never stopped seeking effective methods for information storage. From rocks to paper, and through the past several decades of using computer disks, USB sticks, and on to the thin silicon "chips" and "cloud" storage of today, it would seem that we have reached an era of efficiency for managing innumerable and ever-expanding data. Astonishingly, when tracing this technological path, one realizes that our ancient methods of informational storage far outlast paper (10,000 vs. 1,000 years, respectively), let alone the computer-based memory devices that only last, on average, 5 to 25 years. During this time of fast-paced information generation, it becomes increasingly difficult for current storage methods to retain such massive amounts of data, and to maintain appropriate speeds with which to retrieve it, especially when in demand by a large number of users. Others have proposed that DNA-based information storage provides a way forward for information retention as a result of its temporal stability. It is now evident that DNA represents a potentially economical and sustainable mechanism for storing information, as demonstrated by its decoding from a 700,000 year-old horse genome. The fact that the human genome is present in a cell, containing also the varied mitochondrial genome, indicates DNA's great potential for large data storage in a 'smaller' space.
Keywords: DNA; Animals; ukládání a vyhledávání informací; koně; Information Storage and Retrieval; Horses; zvířata